Lebrikizumab is associated with improvements in patient-reported symptoms and quality-of-life measures across Eczema Area and Severity Index response categories: pooled results from phase-3 randomized ADvocate1 and ADvocate2 studies in patients with moderate-to-severe atopic dermatitis - Andrew Blauvelt; Leon Kircik; Todd Schlesinger; Evangeline Pierce; Russel Burge; Michael Behling; Amber Reck Atwater; Hany ElMaraghy; April Armstrong (Journal of Dermatological Treatment)
Background Lebrikizumab monotherapy significantly improved signs and symptoms in patients with moderate-to-severe atopic dermatitis (AD) in phase 3 Advocate1 and ADvocate2 studies.Objective To evaluate improvements in patient-reported symptoms and quality-of-life (QoL) measures by Eczema Area and Severity Index (EASI) response categories using pooled Advocate1 and ADvocate2 data (post hoc analysis).Methods In the 52-week (W) (16-W induction + 36-W maintenance) double-blind, placebo-controlled ADvocate1 and ADvocate2 studies, patients were randomized (2:1) to receive subcutaneous lebrikizumab 250 mg or placebo every 2 weeks. Investigator Global Assessment (IGA) 0/1 and improvements in QoL outcomes were assessed at W16 among lebrikizumab-treated patients.Results At W16, 564 patients were categorized by EASI response (EASI <50: 32.8%; EASI ≥50–<75: 13.8%; EASI ≥75–<90: 20.2%; EASI ≥90: 33.2%). Patients with higher EASI responses showed higher IGA 0/1 response rates (EASI ≥75–<90: 37.7% and EASI ≥90: 86.1%). Pruritus NRS (least squares mean range: −1.5 to −4.4), sleep-loss score (−0.6 to −1.6), and Dermatology Life Quality Index (−3.3 to −10.6) improved across EASI response categories (p < 0.001). Anxiety and depression scores improved for most EASI response categories (p < 0.01).Conclusion Lebrikizumab-treated patients with moderate-to-severe AD showed improved symptoms and QoL across EASI response categories at W16, with greater improvements observed in patients with higher EASI responses.